Covariance-Driven Structural Model Dataset on Infrastructure Resilience and Community Satisfaction in Coastal Reclamation Regions of Kota Kinabalu - Wilson Rangga, Anthony Jiram; Irwan, Sanjaya; Amanda Sophie, Junim; Azizah, Ismail; Fitriyah, Razali (European Organization for Nuclear Research (CERN), 2025)
This dataset contains quantitative survey data used to examine the relationship between infrastructure resilience and community satisfaction in reclaimed coastal areas of Kota Kinabalu, Malaysia. The data support the study titled “A Covariance-Driven Structural Model of the Nexus Between Infrastructure Resilience and Community Satisfaction in the Coastal Reclamation Regions of Kota Kinabalu.” The dataset includes responses on five infrastructure dimensions, which are network systems, ecological environment and land use, transportation, energy and urban disaster reduction. The dataset also includes community satisfaction indicators used in the covariance-based structural equation model. The dataset enables replication of the CBSEM analysis reported in the article. It provides evidence for assessing the effects of infrastructure conditions on community well-being in coastal environments exposed to sea-level rise, erosion and extreme weather events. The dataset supports research on urban resilience, coastal development and sustainable urban policy.